Moseley's Life in Ruins: The Excavation of Lot 34 and its Structural Remains at Brunswick Town - Gutierrez, Grace D. (East Carolina University, 2018)
During excavations at Brunswick Town in 1959, an anomalous feature was uncovered and interpreted as a rammed earth foundation on politician Edward Moseley's property. However, it was never fully investigated. This style of construction would have been atypical of the time and region in which it was constructed. Due to its anomalous nature and limited investigation, the structure on Moseley's Lot 34 became the focus of East Carolina University's 2017 Summer Field School. During the field school, excavations unearthed a concentration of mortar and brickbats, under which a brick pier was located. The existence of the building pier would seem to refute the existence of a foundation constructed of rammed earth. The subsequent analysis of the recovered artifact assemblage reflected Moseley's elite status and provided information regarding the fate of Lot 34 following Edward Moseley's death in 1749.
Keywords: Brunswick (Brunswick County, N.C.)--History; Excavations (Archaeology)--North Carolina--Brunswick County; Historic sites--North Carolina--Brunswick County; Moseley, Edward, 1682-1749